Produção de uma fração concentrada em alfa-amilase salivar humana (HSA) como alvo para descoberta de novos inibidores e fracionamento do extrato hidroalcóolico da casca de Pouteria sp - Gouveia, Neire Moura de (2008)
CHAPTER II: The alpha-amylases (α-1,4-D-glucan-4-glucanohydrolases, EC 3.2.1.1) are enzymes responsible for the digestion of carbohydrates and are found in saliva and in the pancreatic juice. The primary sequences of the salivary (HSA) and pancreatic (HPA) alpha-amylases show structural similarity of 99%. This standart homology suggests that the HSA can be target of experimental studies of the digestion of carbohydrates inhibition, besides studies showed that potential inhibitors have similar behavior to HPA and HSA. Considering the benefits of noninvasive collection of saliva in relation of pancreatic juice, in this present study obtained a fraction called HSA-CTI. Preparations of the crude extract of the bark of Pouteria sp. was tested about the inhibitory effect of enzymatic activity of the HSA-CTI. Samples of saliva were frozen for 48h, centrifugation and the supernatant was subjected to chromatography in Q-Sepharose column (QS-column) equilibrated in 50mM Tris-HCl buffer at pH 8.0 containing 10mM EDTA and 10mM EGTA. The bound proteins were eluted from QS-column with a gradient concentration of NaCl (0-1M). SDS-PAGE, Western blotting assays and amylase activity measured were performed of the obtained fractions. The HSA-CTI fraction not interacted with the column, and thus prepared by lyophilization and stored in the frozen until realization of the inhibition assays. Aqueous preparations for infusion (EAP-C), deccotion (EAP-C), hydroalcoholic (EHP-C) and ethanolic (EEP-C) of the stem bark extract (10mg/mL in DMSO) have assays by pre-incubation at 10 and 30min at 37ºC with the HAS-CTI (1:10). Only the polypeptide of 56Kda, abundant in the fraction, exhibited cross-reaction with anti-HSA antibody. The assay inhibition showed that stem bark extract has effective in to inhibit the HSA-CTI activity. These results indicate that the HSA-CTI can be obtained by a rapid chromatography method can be used in tests of inhibition from plant extracts. The extract of Pouteria sp. presented as a potential candidate for studies of fractionation and discovery of new substances with activity on these enzymes. CHAPTER III: Preliminary studies about extracts from plants of the kind of Pouteria (Sapotaceae) deal their potential to inhibit human alpha-amylase. These studies may involve the discovery of new sources to reduce post-prandial hyperglycemia, important in the treatment of diabetes and obesity. The active components of Pouteria sp. are still mostly unknown, therefore, the present study fractionated and investigated the substances present in the extract of hydroalcoholic Pouteria sp. with the potential inhibitory on the salivary amylase in vitro. The extract has fractionated in Sephadex LH 20 column equilibrated in methanol and washed with water following by acetone. All the fractions (POUN) was assayed to inhibity the alpha-amylase in vitro. POUN 2 and 3 fractions have injected in semipreparative HPLC (Supecolsyl LC-18 column, mobile phase methanol: water) and analyzed in analytical HPLC (Supecolsyl LC-18 Sp column, mobile phase methanol: acetic acid 0.1%). Assay of inhibition showed that fraction POUN7 exhibited inhibition similar of the crude extract with 40.22% and fractions POUN 2 and 3 exibited inhibition with 15% of the amylase activity. The fraction POUN7 has 48.81% of the constitute it in tannin and represent 35% of the composition of extract. The stem bark crude extract Pouteria sp. have composition it rich in tannin, in addition this extract is potential to others studies, due to this substances have involvement in others therapeutic function.